Conjugated Polymers as a New Class of Dual-Mode Matrices for MALDI Mass Spectrometry and Imaging - Horatz, Kilian; Giampa, Marco; Karpov, Yevhen; Sahre, Karin; Bednarz, Hanna; Kiriy, Anton; Voit, Brigitte; Niehaus, Karsten; Hadjichristidis, Nikos; Michels, Dominik L.; Lissel, Franziska (Journal of the American Chemical Society, 2018)
Matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) and MALDI MS imaging are ubiquitous analytical methods in medical, pharmaceutical, biological, and environmental research. Currently, there is a strong interest in the investigation of low molecular weight compounds (LMWCs), especially to trace and understand metabolic pathways, requiring the development of new matrix systems that have favorable optical properties and a high ionization efficiency and that are MALDI silent in the LMWC area. In this paper, five conjugated polymers, poly[N,N'-bis(2-octyldodecyl)-naphtalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5'(2,2'-bithiophene) (PNDI(T2)), poly(3-dodecylthiophene-2,5-diyl) (P3DDT), poly[2,3-bis(3-octyloxyphenyl)quinoxaline-5,8-diyl]-alt-(thiophene-2,5-diyl) (PTQ1), poly[N,N'-bis(2-octyldodecyl)-isoindigo-5,5'-diyl]-alt-5,5'(2,2'-bithiophene) (PII(T2)), and poly(9,9-di-n-octylfluorenyl-2,7-diyl) (P9OFl) are investigated as matrices. The polymers have a strong optical absorption, are solution processable, and can be coated into thin films, allowing a vast reduction in the amount of matrix used. All investigated polymers function as matrices in both positive and negative mode MALDI, classifying them as rare dual-mode matrices, and show a very good analyte ionization ability in both modes. PNDI(T2), P3DDT, PTQ1, and PII(T2) are MALDI silent in the full measurement range (>m/z = 150k), except at high laser intensities. In MALDI MS experiments of single analytes and a complex biological sample, the performance of the polymers was found to be as good as two commonly used matrices (2,5-DHB for positive and 9AA for negative mode measurements). The detection limit of two standard analytes was determined as being below 164 pmol for reserpine and below 245 pmol for cholic acid. Additionally P3DDT was used successfully in first MALDI MS imaging experiments allowing the visualization of the tissue morphology of rat brain sections.
CRIS-Team Scopus Importer:2022-04-14